RELATIONSHIP BETWEEN AGGRESSIVE BEHAVIOR AND DEPRESSION AMONG JOHOR PRISON FINAL PRISONERS - Vinodh Elamkovam; Saralah Devi Mariamdaran (Polteknik Ilmu Pemasyarakatan, 2021)
The issue of depression among prisoners has received attention from researchers in the field of imprisonment and correctional services in recent times. Various studies have been conducted to answer the questions that arise in the issue of depression especially among final prisoners. Therefore, this study was conducted to examine the relationship between depression and aggressive behavior among final inmates in Johor State Prison. This quantitative study used a questionnaire and involved a total of 127 respondents consisting of final inmates from three Johor State Prison institutions. The collected data were analyzed using Statistical Package for Social Science (SPSS) version 20.0. The findings of the study found that there was a relationship between depression and aggressive behavior of final inmates in Johor State Prison. While the results of t test analysis found that there is no difference in aggressive behavior and depression according to the citizenship status of final inmates while the results of ANOVA test analysis found that there is no difference in aggressive behavior and depression according to age of final inmates in Johor State Prison. Thus, the formation of discipline and emphasis on the personality aspects of the final prisoner should be focused by the prison institution with the aim of producing final prisoners who can return to the basics if released later.